Importance of intelligent rooms for energy savings in the hotel industry - Krstinić Nižić, Marinela; Karanović, Goran, ekonomist; Ivanović, Saša, ekonomist (2008)
Abstract: Thanks to the application of new technologies which enable rational use of energy, hotel company can now reduce power consumption per night compared to the average expenses of hotels of same quality. This has been enabled by the implementation of so- called intelligent hotel-room system, which includes control system and optimal consumption of energy and water, along with regulation and optimal use of heating and cooling system. The underlying assumption of this report states that the efficacy of energy is not the result of the investment in sophisticated technology only, but is also modified by monitoring and active management of energy consumption. Therefore, it requires specialist knowledge and maintenance workers training. Thus, company's ecological orientation demands an additional advance in the domain of human resources administration. From the economic standpoint, the report deals with the research in economic effects of intelligent hotel room based on the research in concrete examples in hospitality industry. Furthermore, the paper analyses growing demands and problems in energy supply system of large tourist facilities which have to provide an ultimate solution to energy consumption. In conclusion, there is a need of hotel companies to conduct their business in accordance with ecological demands
Bibliografske bilješke uz tekst ; bibliografija: 20 jed. ; internetski izvori
Keywords: Hotelijerstvo -- Upravljanje energijom